2007
DOI: 10.1107/s1600536807002322
|View full text |Cite
|
Sign up to set email alerts
|

(E)-2-{1-[(4-Ethoxyphenyl)imino]ethyl}phenol

Abstract: Key indicatorsSingle-crystal X-ray study T = 296 K Mean (C-C) = 0.002 Å R factor = 0.038 wR factor = 0.116 Data-to-parameter ratio = 13.6For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
3
2
0
Order By: Relevance
“…The C7-N1 [1.296 (4) Å] and C22-N2 [1.296 (4) Å] bond distances are of double-bond character, whereas, the C2-O1 [1.344 (4) Å] and C17-O4 [1.342 4Å] distances are single bonds. These distances are similar to other values reported in the literature [1.2889 (15) and1.2891 (14) Å for C=N and 1.3486 (16) and 1.3443 (15) Å for C-O, respectively; Petek et al (2007)]. Both molecules are not planar; the dihedral angle between the aromatic rings are 24.6 (2) and 30.30 (13) °, respectively.…”
Section: S1 Commentsupporting
confidence: 88%
“…The C7-N1 [1.296 (4) Å] and C22-N2 [1.296 (4) Å] bond distances are of double-bond character, whereas, the C2-O1 [1.344 (4) Å] and C17-O4 [1.342 4Å] distances are single bonds. These distances are similar to other values reported in the literature [1.2889 (15) and1.2891 (14) Å for C=N and 1.3486 (16) and 1.3443 (15) Å for C-O, respectively; Petek et al (2007)]. Both molecules are not planar; the dihedral angle between the aromatic rings are 24.6 (2) and 30.30 (13) °, respectively.…”
Section: S1 Commentsupporting
confidence: 88%
“…respectively] are comparable to corresponding values observed in a similar phenol-imine tautomeric structures (e.g. Petek et al, 2007), while different geometry is observed in the case of zwitterionic molecules (Elmali et al, 2001;Yüce et al, 2006)…”
Section: Data Collectionsupporting
confidence: 84%
“…For general properties of Schiff base compounds, see: Weber et al (2007); Chen et al (2008). For related structures, see: Elmali et al (2001); Yü ce et al (2006); Petek et al (2007). Monoclinic, P2 1 =c a = 13.4640 (13) Å b = 7.4450 (6) Å c = 15.4090 (11) Å = 116.660 (6) V = 1380.4 (2) Å 3 Z = 4 Mo K radiation = 0.08 mm À1 T = 293 K 0.20 Â 0.20 Â 0.20 mm…”
Section: Related Literaturementioning
confidence: 99%
“…1) and demonstrates atom receives the phenol-imine tautomeric shape with a solid intra molecular O-H···N hydrogen linkage. The C-N and C-O bond lengths [1.296 and 1.324 Å] are practically identical to comparing esteems saw in a comparative phenolimine tautomeric geometry shape [25], while diverse geometry is seen on account of zwitterionic particles [26,27]. Phenyl and naphthyl rings are obviously planar and the dihedral point is 8.98 (9) Boghaei and Lashanizadegan [28] had illustrated the preparation and significant properties of Cu(II) and Ni(II) complexes of novel non-symmetrical N2O2 azomethine ligand (Fig.…”
Section: Introductionsupporting
confidence: 61%